Direct Simulation Monte Carlo Procedure for Molecular Collision Energy Transfer in Quantum Nature - Liang, Jie; Li, Zhihui; Fang, Ming; Tang, Xiaowei (Journal of Environmental Accounting and Management, 2026)
In order to precisely simulate the thermodynamic nonequilibrium feature in hypervelocity streaming and plume expansion flows, the discrete energy transfer procedure considering quantum effect in direct simulation Monte Carlo method is presented. The formulas of rotational energy for non-rigid rotator model and vibrational energy for anharmonic oscillator model on diatomic molecules are given. The calculation of quantum energy levels at equilibrium distribution is described. The energy transfer models of rotation-translation and vibration-translation as well as their implementation are derived. Two dimensional hypersonic flow around a cylinder of Nitrogen with different flight speeds is computed and analyzed. The comparison of the thermodynamic nonequilibrium process between continuous and discrete energy modes indicate the necessity of energy transfer model considering quantum effect for precise simulation of the thermodynamic nonequilibrium feature in high temperature flow field. The simulation of vacuum plume expansion also demonstrates the significant quantum effect of rotation mode.